The best execution of the DuoStim strategy (double stimulation in the follicular and luteal phase of the same ovarian cycle) in patients who are poor ovarian responders - Yanqun Luo; Li Sun; Mei Dong; Xiqian Zhang; Li Huang; Xiulan Zhu; Yingqi Nong; Fenghua Liu (BMC, 2020)
Abstract Background Patients found to be poor ovarian responders (POR) are a challenging patient population for any assisted reproduction technology. Despite attempts at various controlled ovarian stimulation schemes, reproductive outcomes in this patient population have not improved. In recent years, the DuoStim protocol (both follicular and luteal phase stimulation during the same menstrual cycle) has shown a potential for use in patients with POR. Methods This retrospective study reviewed the medical records of 304 women who were diagnosed as POR and underwent the DuoStim protocol. We compared follicular phase stimulation (FPS) data and luteal phase stimulation (LPS) data of the same patients. We also compared the effects of different trigger drugs including urine human chorionic gonadotropin (uHCG; 10,000 IU), recombinant human chorionic gonadotropin (rHCG; 250 μg), and gonadotropin-releasing hormone agonist (GnRH-a; 0.2 mg) at the FPS and LPS stages. Results POR undergoing the DuoStim protocol resulted in a significantly higher number of oocytes retrieved, normal fertilised oocytes, cleaved embryos, cryopreserved embryos, and good quality embryos at the LPS stage than at the FPS stage. Trigger drugs at the FPS stage did not affect the FPS stage data. Regardless of the stage, rHCG and GnRH-a yielded significantly more cryopreserved embryos and good quality embryos than uHCG. Conclusion The use of GnRH-a or rHCG as the trigger drug may be better than uHCG in both the FPS and LPS stages for POR undergoing the DuoStim protocol. This will increase the number of good quality embryos at the LPS stage. We found that the LPS stage results in more oocytes (and therefore more embryos) than the FPS stage.